Assessment of possibility of dumping site selection for dredged materials from shipping channels in Hai Phong coastal waters - Lan, Tran Dinh; Vinh, Vu Duy; Huong, Do Thi Thu; Khanh, Do Gia (Vietnam Journal of Marine Science and Technology, 2020)
In order to keep essential depths in shipping channels to and from Hai Phong ports, regular dredging activities are maintained with about 3.6 million tons of sediments per year. Due to almost all the sediments of dredged material in the channels are composed of mud and silt, they are not easy to be used for land filling or other purposes. Moreover, disposing these materials on land is facing difficulties because of requiring the design and construction of dikes, requiring compaction and drainage of dumped materials. Therefore, disposal of dredged material from shipping channels in Hai Phong sea has become urgent. Based on integrated approach, the combination of numerical modeling and multicriteria decision analysis-GIS (natural condition, socio-economic and environment-ecosystem conditions) was made and the most suitable dumping sites were proposed in the regions with water depth ranging between 18–27 m. Their total receiving capacity was estimated about 206 million tons for 40–50 years.